Universal molecular structures in natural dissolved organic matter - Maren Zark (Nature Portfolio, 2018)
Dissolved organic matter (DOM) in aquatic systems is among the most complex molecular mixtures known. Here the authors show that a major component in DOM is molecularly indistinguishable in marine and freshwater environments, which could reflect universal mechanisms behind long-term DOM turnover.